Covalent Reactions on Chemical Vapor Deposition Grown Graphene Studied by Surface-Enhanced Raman Spectroscopy - Kovaříček, Petr; Bastl, Zdeněk; Valeš, Václav; Kalbac, Martin (Chemistry (Weinheim an der Bergstrasse, Germany), 2016)
Graphene is a material of unmatched properties and eminent potential in disciplines ranging from physics, to chemistry, to biology. Its advancement to applications with a specific function requires rational design and fine tuning of its properties, and covalent introduction of various substituents answers this requirement. We challenged the obstacle of non-trivial and harsh procedures for covalent functionalization of pristine graphene and developed a protocol for mild nucleophilic introduction of organic groups in the gas phase. The painstaking analysis problem of monolayered materials was addressed by using surface-enhanced Raman spectroscopy, which allowed us to monitor and characterize in detail the surface composition. These deliverables provide a toolbox for reactivity of fluorinated graphene under mild reaction conditions, providing structural freedom of the species to-be-grafted to the single-layer graphene.
Keywords: surface chemistry; nucleophillic substitution; Raman spectroscopy; nanomaterials; graphene